Security of Credentials: Algorithms and Techniques for Storing Passwords - Piotr KONTOWICZ (Communications of International Proceedings, 2024)
The developers and administrators face major challenges in assuring the security of the users passwords within the applications as a result of growing breaches and cyber attacks. Improper mechanisms of storage may lead to serious security consequences for password data protection. The article is directed to the presentation of modern approaches and best practices concerning password storing. It discusses the most relevant password storage approaches, considering the risks involved and presenting options and their aftermath. The paper provides a step by step guide on how user passwords should be securely stored.
Keywords: Password security; cryptographic hash functions; password storage.